The lady's handbook for her mysterious illness : a memoir - Ramey, Sarah (Doubleday, 2020)
"The funny, defiant memoir of Sarah Ramey's years-long battle with a mysterious illness that doctors thought was all in her head--but wasn't. A revelation and an inspiration for millions of women whose legitimate health complaints are ignored. In her darkly funny and courageous memoir, Sarah Ramey recounts the decade-long saga of how a seemingly minor illness in her senior year of college turned into a prolonged and elusive condition that destroyed her health but that doctors couldn't diagnose or treat. Worse, as they failed to cure her, they hinted that her problems were all in her head. The Lady's Handbook for Her Mysterious Illness is a memoir with a mission: to help the millions of (mostly) women who suffer from unnamed or misunderstood conditions: autoimmune illnesses like fibromyalgia and chronic fatigue syndrome, chronic Lyme disease, chronic pain, and many more. Sarah's pursuit of a diagnosis and cure for her own mysterious illness becomes a page-turning medical mystery that reveals a newly emerging understanding of modern illnesses as ecological in nature. Her book will open eyes, change lives, and ultimately change medicine"--